2005
DOI: 10.1007/s10157-004-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

Predominant tubulointerstitial nephritis in a patient with systemic lupus nephritis

Abstract: In most cases of systemic lupus erythematosus (SLE), glomerular lesions are the main renal complication. Although tubulointerstitial lesions are often associated with severe glomerular lesions, predominant or isolated tubulointerstitial injury in the presence of minimal glomerular abnormalities with SLE, so-called predominant tubulointerstitial lupus nephritis, is rare. Only ten cases are reported in the English literature. Herein, we describe the case of a 64-year-old man with SLE who presented with acute ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 17 publications
1
38
0
1
Order By: Relevance
“…While SLE patients can have predominant tubulointerstitial lupus nephritis, characterized by predominant or isolated tubulointerstitial renal damage and minimal glomerular abnormalities, it is quite rare (3). To our knowledge, only 13 cases of predominant tubulointerstitial lupus nephritis have been reported in the English literature (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We herein describe the case of an 80-year-old man who had a mild renal dysfunction with increased antidsDNA antibody levels.…”
Section: Introductionmentioning
confidence: 93%
“…While SLE patients can have predominant tubulointerstitial lupus nephritis, characterized by predominant or isolated tubulointerstitial renal damage and minimal glomerular abnormalities, it is quite rare (3). To our knowledge, only 13 cases of predominant tubulointerstitial lupus nephritis have been reported in the English literature (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We herein describe the case of an 80-year-old man who had a mild renal dysfunction with increased antidsDNA antibody levels.…”
Section: Introductionmentioning
confidence: 93%
“…However, in systemic lupus erythematosus, some cases show severe tubulointerstitial nephritis with minimal glomerular changes or mild mesangial proliferation (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), although rare. To date, 12 cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Saeki (3), Kawano (13) and Yoshita (14) et al each evaluated at least 20 patients with IgG4-RKD in their series using histological evaluations of light and immunohistochemical modalities without electron microscopy. To date, observations with electron microscopy have been restricted to limited case reports (1,2,6,7,(15)(16)(17). Recently Yamaguchi et al (18) comprehensively reported the ultrastructural findings of 10 cases.…”
Section: Discussionmentioning
confidence: 99%